2009
DOI: 10.1039/b817203j
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on the role of metals in diabetes: past findings and possible future directions

Abstract: Jennifer Meyer got her bachelor's degree in chemistry and mathematics from Central Michigan University in 2005. She began her doctoral studies in the fall of 2005 and is currently a graduate student in the labs of Dr Dana Spence at Michigan State University. Jennifer's research has focused on defining new roles for C-peptide and its effect on erythrocytes as it pertains to diabetic complications. Her work has been published in both clinical and chemical journals. After graduation, she hopes to pursue a career … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 155 publications
(153 reference statements)
1
50
1
2
Order By: Relevance
“…Patients with diabetes suffer from hypozincemia as a result of failure of ␤-cell production, which finally affects insulin levels [19]. Our results are consistent with this finding as we detected a 1.8-fold higher Zn concentration in healthy rats than in diabetic ones after sodium tungstate treatment (Table 2).…”
Section: W Accumulation In Diabetic and Healthy Rats After Treatment supporting
confidence: 91%
See 1 more Smart Citation
“…Patients with diabetes suffer from hypozincemia as a result of failure of ␤-cell production, which finally affects insulin levels [19]. Our results are consistent with this finding as we detected a 1.8-fold higher Zn concentration in healthy rats than in diabetic ones after sodium tungstate treatment (Table 2).…”
Section: W Accumulation In Diabetic and Healthy Rats After Treatment supporting
confidence: 91%
“…It has been reported that levels of GSH, an abundant antioxidant metabolite present in cells at mM level, are lower in patients suffering from diabetes [21]. Metals like Cu, Mn, Mg, Fe, Se, V, Cr and Zn have been proposed to indirectly participate in the reversal of oxidative stress [19], with some establishing complexes with GSH, as shown for V [22].…”
Section: Interaction Of W With Glutathionementioning
confidence: 99%
“…Quarterman et al [45] reported that diet induced zinc deficiency in rats resulted in a decrease in the ability of the pancreas to secrete insulin in response to a glucose load. Meyer and Spence [46] indicated that decreased zinc in the pancreas may reduce the ability of the islet b-cells to produce and secrete insulin and zinc deficiency is positively correlated with diabetes and may also affect the progress of Type 2 diabetes [47].…”
Section: F CLmentioning
confidence: 99%
“…Following collection of plasma samples, organs (liver, muscle, adipose, pancreas, femur, and kidney) were dissected, weighed and heated repeatedly at approximately 200°C with 60% HNO 3 , 60% HClO 4 , and 30% H 2 O 2 in 50 ml tall beakers. When the residues became white powder, the samples were dissolved in 1% HNO 3 . The Zn concentrations were determined by a graphite furnace atomic absorption spectrometer (AAS; AA-630 and GFA-EX7i, Shimadzu Co., Kyoto, Japan).…”
Section: Administration Of Zinc Complexes In Kk-a Y Micementioning
confidence: 99%
“…2) For many years, the relationship between diabetes and biometals such as vanadium, copper, and zinc ions has been recognized and discussed. 3) We have developed anti-diabetic metal complexes as new candidates for hypoglycemic agents. Since 2000, we have proposed several types of zinc(II) (Zn) complexes with various coordination modes, [4][5][6][7][8] in which Zn complexes with Zn(O 4 ) and Zn(N 2 O 2 ) coordination environments showed anti-diabetic effect on oral administration.…”
mentioning
confidence: 99%